Pemanfaatan Pliek U (Bumbu Khas Aceh) sebagai Krim Antibakteri - Yuni Trisnawita; Elisa Putri; Muhammad Ridha Al Ikhsan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the antibacterial activity of Pliek U ethanol extract cream against Staphylococcus aureus. The method was an experimental method with a completely randomized design (CRD) on five treatments, namely positive control, negative control, F1, F2, and F3, each with four repetitions. Antibacterial testing was carried out using the disc diffusion method. The results showed that the average diameters of F1, F2 and F3 were 12.65 mm, 14.9 mm and 12.92 mm, which were included in the solid antibacterial category in inhibiting the activity of Staphylococcus aureus bacteria. Pliek U can be formulated as a cream preparation, meets the requirements for quality tests for cream preparations and has met SNI standard parameters. In conclusion, Pliek U ethanol extract cream has antibacterial activity with the most optimum effectiveness at a concentration of 5%. Keywords: Antibacterial, Cream, Pliek U, Staphylococcus aureus